Study on Packaging Elements That Affect Consumer Purchase Decisions of Body Wash Products in Klang Valley, Malaysia - Lai, Wun Yen (2014)
Packaging plays an important role in today’s competitive market as a means of attracting consumer attention, due to the growth of self-service retail and other changes in consumer buying patterns. The main objective of this thesis is to examine packaging elements that can influence consumer purchase decisions of body wash products in the Klang Valley, Malaysia, in order to have a better understanding of which packaging elements primarily affect shoppers’ purchasing judgements. To pursue these objectives, the authors developed a research framework for packaging which divides the main objective into two sub-objectives. The first of these seeks to determine the influence of visual packaging elements on consumer purchase decisions, while the second focuses on the influence of informational packaging elements on such decisions. Independent variables like graphics and color, shape and size are categorized under visual elements, while informational elements include product information and technology image. The study adopts a descriptive research design methodology. Data was collected through survey questionnaires from 385 respondents selected at random. The data analytical methods used in this thesis are descriptive analysis, reliability analysis and multiple regression analysis. A descriptive analysis analyzes the respondents’ demographic profile and consumer perceptions of packaging. A reliability test was then carried out to check for consistency based on the average correlation between variables. Finally, a multiple regression analysis seeks to identify the relationship between consumer purchase decisions and two independent variables, namely visual elements and informational elements. This research confirms that packaging elements can have an important influence on consumer purchase decisions of body wash products. Its findings further show that informational elements are more likely to influence consumers in their purchase decisions than visual elements.